PSEUDO-OBJECTIVE MOTIVATION IN MARIAH STEWART’S MERCY STREET AND CRY MERCY - Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2013)
This article discusses on popularfiction applying Bakhtin’s theory, that is pseudo-objective motivation. Thismotivation is writing composition which author applies and it relates toideology. Here, I found that the charaters of Mercy Street and Cry Mercypractice capitalism ideology. This ideological practices becomes norm in thenovels, because they think wrong if they do not practice it. The norms orvalues are known as work ethics. The norms are individualism, working hard,discipline, frugality, honest, and independent. Pseudo-objective motivation iscategorized into common view, subordinate conjunction and linking words, andcollective voice. These categories are found in the novels.KEY WORDS: pseudo-objectivemotivation, Bakhtin, popular fiction, capitalism.